Occult Hip Prosthetic Loosening Diagnosed by [18F] Fluoride-PET/CT - Ullmark, Gösta (Arthroplast Today, 2020)
BACKGROUND: Positron emission tomography using the [18F] fluoride metabolite combined with computerized tomography (F-PET/CT) can be used to analyze the metabolic status of the periprosthetic bone after surgery for total hip arthroplasty. METHODS: To obtain normal PET referent values, 44 patients with 5 models of well-functioning hip prosthetic components were analyzed by F-PET/CT, radiography, and clinical score. Another group of patients having painful total hip arthroplasty, but whose radiography showed no conclusive signs of loosening, was analyzed by F-PET/CT scans before revision surgery. RESULTS: Preoperative median F-PET scores of the bone metabolic activity were 6.65 (3.3-9.0) for the painful stem group and 1.85 (1.2-3.9) (P < .01) for the referent group having the same stem model. At revision surgery, the stems in the painful group were assessed to be loose. At 2-year follow-up, the revised patients were all pain free. CONCLUSION: F-PET/CT may be a new diagnostic tool for assessing occult loose stems that are not seen by radiography.